GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Dust transport and impacts on secondary aerosol formation: Contrasting strong dust and floating dust events - Yanfen Lin; Qingyan Fu; Ziwei Liu; Zhijian Ding; Fan Yang; Ali Darvishi Boloorani; Cheng Huang; Juntao Huo; Qian Wang; Jia Chen; Qiongzhen Wang; Sabur F. Abdullaev; et al. (Atmospheric Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Ecological functions and bioaugmentation applications of stress-resistant microorganisms under inhibited anaerobic digestion environments - Chao Yang; Pinjing He; Andreia F. Salvador; Wei Peng; Hua Zhang; Haowen Duan; Fan Lü (Chemical Engineering Journal, 2026)

How heating rate governs microcrack-induced damage revealed by X-ray computed tomography? - L. F. Fan; H. Y. Fan; B. Qiu; Q. H. Yang (Bulletin of Engineering Geology and the Environment, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Triggering mechanisms and dynamics of an off-season rainfall-induced rock avalanche in the Wumeng Mountains, China - Guiping Xia; Xiaoyi Fan; Ying Zhou; Anjiang He; Jiaqin Chen; Huan Liu; M. F. Hassanein (Landslides, 2026)

Heavy metals and per- and polyfluoroalkyl substances in breast milk: associations with infant birth outcomes in an E-waste recycling area - Yueyuan Fan; Hui Wang; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Cheng‑Sheng Zhu; Xian Liang Sun (Environmental Geochemistry and Health, 2026)

Three-dimensional dust distribution and transport over the northern hemisphere dust belt: Insights from lidar observations - Ruiqi Tan; Tianhe Wang; Ying Han; Jingtao Li; Jingyi Tang; Sichen Wang; Ali Mamtimin; Fan Yang; Chenglong Zhou; Bakhriddin E. Nishonov; Mansur O. Amonov; Sabur F. Abdullaev (Atmospheric Research, 2026)

The science of urban informatics - Wenzhong Shi; Anshu Zhang; Fan Shi; Michael Batty; Michael F. Goodchild (Science Bulletin, 2026)

Engineered Artificial Rock Designed to Replicate Sandstone Wave Behavior - L. F. Fan; Y. Q. Hu; Q. H. Yang; G. F. Zhao; S. Q. Yang (Rock Mechanics and Rock Engineering, 2026)

Respirable mineral fibres in leaf surface dust: Micro-characterisation and evidence of a geogenic origin - Wenxia (Wendy) Fan; Kim N. Dirks; Alessandro F. Gualtieri; Paul G. Young; Ayrton Hamilton; Janki P. Patel; Timothy D. Christopher; Jennifer A. Salmond (Chemosphere, 2026)

Retraction notice to “Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community” [Sci. Total Environ. 929 (2024) 172632] - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2026)

Vascular Organoids Derived from Capillary malformation-induced Pluripotent Stem Cells Exhibit Disease-Relevant Phenotypes - Vi Nguyen; Anna Harper; Mackenzie Azuero; Isabella Castellanos; Siwuxie He; Marcelo L. Hochman; Camilla F. Wenceslau; Dong-bao Chen; Anil G. Jegga; Yunguan Wang; Daping Fan; J. Stuart Nelson; et al. (Stem Cell Reviews and Reports, 2026)
Capillary malformation (CM) is a congenital vascular anomaly that affects the skin, mucosa, eye, and brain. A major obstacle to mechanistic and drug screening studies for CM has been the lack of preclinical models. In this study, we established vascular organoids (VOs) generated through the self-assembly of vascular lineages of endothelial cells and smooth muscle cells differentiated from CM-induced pluripotent stem cells (iPSC). Within these VOs induced endothelial cells and smooth muscle cells organized into juxtapositions to form vascular branches. CM patient iPSC-derived VOs showed a higher density of endothelial and smooth muscle cell populations and greater vascular branch lengths as compared with VOs derived from iPSCs generated from healthy skin biopsies. Overall, this study represents the first disease-relevant VO model of CM, providing a valuable platform for future mechanistic studies and drug screening.

Mid-Seral Thinned Stands in Pacific Northwest Coastal Forests Show Enhanced Floral and Bee Diversity without Increased Parasite Prevalence in Wild Bees - Jesse J. Fan Brown; Katie Moriarty; Rose McDonald; Lincoln R. Best; Jocelyn F. Zorn; Lauren C. Ponisio (Journal of Forestry, 2026)
Management practices, such as forest thinning, may support bee communities by increasing the abundance and diversity of floral resources in forest ecosystems. However, these enhancements could also concentrate foraging bees, potentially facilitating disease spread. In this study, we surveyed understory plant and bee communities and the prevalence of bee parasites across forest stands of different ages and management histories in the coastal Pacific Northwest, including early seral stands, two size classes of mid-seral thinned stands, and mature unthinned stands. We found that both categories of thinned stands supported levels of flowering plant diversity and abundance and overall bee abundance comparable to those found in early seral stands, although bee diversity was highest in early seral stands. In contrast, mature stands exhibited substantially less abundant and diverse plant-pollinator communities than early seral stands. Though we expected that thinned stands would primarily affect flowering plants and bees through reduced canopy cover, within thinned stands increased canopy openness was only associated with a modest increase in floral abundance. We did not observe a strong influence of canopy openness on floral diversity or bee diversity and abundance. The prevalence of the common parasite genus Crithidia spp. was not strongly related to bee or floral community characteristics but was negatively related to bumble bee foraging distance capacity. These findings suggest that thinned forests have enhanced forage opportunities for bees but do not exacerbate the spread of disease—offering a promising management strategy for sustaining healthy pollinator populations in restored forest ecosystems.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Emergency mitigation strategies for the settlement of in-service pile foundations in Permafrost Regions: Application of artificial ground freezing - Changxin Fan; Zhi Wen; Qiang Gao; Alexander F. Zhirkov (Cold Regions Science and Technology, 2025)

Evidence of airborne dispersion of respirable-sized carcinogenic erionite fibres of volcanic origin - Wenxia (Wendy) Fan; Kim N. Dirks; Alessandro F. Gualtieri; Paul G. Young; Ayrton Hamilton; Janki P. Patel; Jennifer A. Salmond (Environmental Research, 2025)

Evolution of unfrozen water distribution in sandstone pores of varying sizes during freeze-thaw cycles with consideration of moisture recharge - L. F. Fan; C. M. Ma; B. Qiu (Bulletin of Engineering Geology and the Environment, 2025)

Interaction of water saturation and freeze-thaw cycles on stress wave attenuation and dispersion in sandstone - Q. H. Yang; L. F. Fan; X. L. Du (Bulletin of Engineering Geology and the Environment, 2025)

The effect of a bench on leakage through a cover: A field and numerical assessment - Felix Y.H. Fan; R. Kerry Rowe; R.W.I. Brachman; Jamie F. VanGulck (Geotextiles and Geomembranes, 2025)

Phragmivirus, a new genus within the family Potyviridae - Alice Kazuko Inoue-Nagata; Ramon Jordan; Jan F. Kreuze; Fan Li; Juan José López-Moya; Kristiina Mäkinen; Kazusato Ohshima; Luisa Rubino; Stephen Wylie (Archives of Virology, 2025)

Complement Inhibition Reduces Early Erythrolysis, Attenuates Brain Injury, Hydrocephalus, and Iron Accumulation after Intraventricular Hemorrhage in Aged Rats - Tianjie Zhang; Fan Xia; Yingfeng Wan; Guohua Xi; Hua Ya; Richard F. Keep (Translational Stroke Research, 2025)

Fluoride-induced stress shapes partial denitrification granules to sustain microbial metabolism - Shenbin Cao; Jinxin Fang; Konrad Koch; Xiaoyan Fan; Hussein E. Al-Hazmi; Rui Du; George F Wells (Water Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Selective production of olefins from methanol over a heteroatomic SAPO-34 zeolite - Zhaodong Zhu; Mengtian Fan; Meng He; Bing An; Yinlin Chen; Shaojun Xu; Tianze Zhou; Alena M. Sheveleva; Meredydd Kippax-Jones; Lutong Shan; Yongqiang Cheng; Hamish Cavaye; et al. (Science Bulletin, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Pore Water Freezing in Sandstone Considering Pore Structure Effects - B. Qiu; L. F. Fan; X. L. Du (Rock Mechanics and Rock Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Effect of backfilling surface settlement trough on waste cover leakage - Felix Y.H. Fan; R. Kerry Rowe; Richard W.I. Brachman; Jamie F. VanGulck (Geotextiles and Geomembranes, 2025)

Investigating the deposition of fibrous zeolite particles on leaf surfaces: A novel low-cost method for detecting the presence of airborne hazardous mineral fibers - Wenxia (Wendy) Fan; Alessandro F. Gualtieri; Kim N. Dirks; Paul G. Young; Jennifer A. Salmond (Journal of Hazardous Materials, 2024)

Exogenous Application of Chitosan Mitigates the Inhibitory Effects of Zinc on the Growth of Wheat Seedlings by Modulating Zn Transport and ROS Scavenging - Lina Fan; Jingjing Zhang; Zhengyang Xu; Qiujuan Jiao; Zihao Song; Peiyi Yu; Deyuan Liu; Gezi Li; Shah Fahad; Zulfiqar Ali Sahito; Mohammed Ali Alshehri; Salah F. Abou-Elwafa; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Improved global estimation of seasonal variations in C3 photosynthetic capacity based on eco-evolutionary optimality hypotheses and remote sensing - Yihong Liu; Jing M. Chen; Mingzhu Xu; Rong Wang; Weiliang Fan; Wenyu Li; Lucas Kammer; Colin Prentice; Trevor F. Keenan; Nicholas G. Smith (Remote Sensing of Environment, 2024)

Phosphorus flux during the Ediacaran: Rooted in continental weathering or pelagic upwelling? - Haifeng Fan; Hongjie Zhang; Wei Wei; Eric.E. Hiatt; Jack F. Ward; Hanjie Wen (Earth and Planetary Science Letters, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Wave attenuation coefficient and wave number of high-temperature granite after water cooling and air cooling - Q. H. Yang; K. C. Yang; G. Y. Li; L. F. Fan; X. L. Du (Bulletin of Engineering Geology and the Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Wave transmission in layered composite rock mass comprising parallel joints and different rock materials - L.F. Fan; X.Y. Shi; M. Wang; F. Jiang (International Journal of Rock Mechanics and Mining Sciences, 2024)

RETRACTED: Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2024)

Aligning health, environment, and cost aspects of diets: Identifying sustainable dietary patterns in China - Hongyi Cai; Elise F. Talsma; Zhiyao Chang; Xin Wen; Shenggen Fan; Pieter Van ’t Veer; Sander Biesbroek (Environmental Impact Assessment Review, 2024)

How do regional and demographic differences in diets affect the health and environmental impact in China? - Hongyi Cai; Sander Biesbroek; Zhiyao Chang; Xin Wen; Shenggen Fan; Pieter van 't Veer; Elise F. Talsma (Food Policy, 2024)

Addressing the gap: advancements in flow forecasting systems for small mountainous catchments - M. R. Fagundes; F. M. Fan; C. H. A. Gama; K. Campagnolo; M. A. Paixão; M. Kobiyama (Natural Hazards, 2024)

Oblique incident seismic P wave propagation through joints containing saturated fluids with different media on both sides - L.F. Fan; F. Jiang; M. Wang; S. Chen (Journal of Applied Geophysics, 2024)

A Short-Bar Combined-Wave Method for Wave Propagation Coefficient Determination - L. F. Fan; Q. H. Yang; M. Wang; X. L. Du (Rock Mechanics and Rock Engineering, 2024)

Efficiency of thermotherapy for eliminating apple rubbery wood virus 2 and other viruses from apple plants - G.-J. Hu; Y.-F. Dong; Z.-P. Zhang; X.-D. Fan; F. Ren (Australasian Plant Pathology, 2024)

Haplotype-based phylogenetic analysis and population genomics uncover the origin and domestication of sweetpotato - Mengxiao Yan; Ming Li; Yunze Wang; Xinyi Wang; M-Hossein Moeinzadeh; Dora G. Quispe-Huamanquispe; Weijuan Fan; Yijie Fang; Yuqin Wang; Haozhen Nie; Zhangying Wang; Aiko Tanaka; et al. (Molecular Plant, 2024)

O-GlcNAc modification of GSDMD attenuates LPS-induced endothelial cells pyroptosis - Fan Yu; Zhen Zhang; Yiping Leng; Alex F. Chen (Inflammation Research, 2024)
Objective Increased O -linked β- N -acetylglucosamine ( O -GlcNAc) stimulation has been reported to protect against sepsis associated mortality and cardiovascular derangement. Previous studies, including our own research, have indicated that gasdermin-D(GSDMD)-mediated endothelial cells pyroptosis contributes to sepsis-associated endothelial injury. This study explored the functions and mechanisms of O -GlcNAc modification on lipopolysaccharide (LPS)-induced pyroptosis and its effects on the function of GSDMD. Methods A LPS-induced septic mouse model administrated with O -GlcNAcase (OGA) inhibitor thiamet-G (TMG) was used to assess the effects of O -GlcNAcylation on sepsis-associated vascular dysfunction and pyroptosis. We conducted experiments on human umbilical vein endothelial cells (HUVECs) by challenging them with LPS and TMG to investigate the impact of O -GlcNAcylation on endothelial cell pyroptosis and implications of GSDMD. Additionally, we identified potential O -GlcNAcylation sites in GSDMD by utilizing four public O -GlcNAcylation site prediction database, and these sites were ultimately established through gene mutation. Results Septic mice with increased O -GlcNAc stimulation exhibited reduced endothelial injury, GSDMD cleavage (a marker of pyroptosis). O -GlcNAc modification of GSDMD mitigates LPS-induced pyroptosis in endothelial cells by preventing its interaction with caspase-11 (a human homologous of caspases-4/5). We also identified GSDMD Serine 338 (S338) as a novel site of O -GlcNAc modification, leading to decreased association with caspases-4 in HEK293T cells. Conclusions Our findings identified a novel post-translational modification of GSDMD and elucidated the O -GlcNAcylation of GSDMD inhibits LPS-induced endothelial injury, suggesting that O -GlcNAc modification-based treatments could serve as potential interventions for sepsis-associated vascular endothelial injury.

Hg isotope evidence for oceanic oxygenation during the Cambrian Explosion - Haifeng Fan; Xuewu Fu; Ruofei Yang; Hanjie Wen; Chunlin Hu; Jack F. Ward; Hongjie Zhang; Hui Zhang; Xingliang Zhang (Geochimica et Cosmochimica Acta, 2023)

Fracture Toughness Anisotropy in Shale Under Deep In Situ Stress Conditions - Q. Zhou; H. P. Xie; Z. M. Zhu; R. He; H. J. Lu; Z. D. Fan; X. F. Nie; L. Ren (Rock Mechanics and Rock Engineering, 2023)

Improving the performance of artificial intelligence models using the rotation forest technique for landslide susceptibility mapping - H. Shen; F. Huang; X. Fan; H. Shahabi; A. Shirzadi; D. Wang; C. Peng; X. Zhao; W. Chen (International Journal of Environmental Science and Technology, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

A Real-Time Visual Investigation on Microscopic Progressive Fatigue Deterioration of Granite Under Cyclic Loading - L. F. Fan; B. Qiu; J. W. Gao; X. L. Du (Rock Mechanics and Rock Engineering, 2023)

Stress-Water Coupling Effects on Failure of Sandstone Based on Real-Time CT Technology - L. F. Fan; B. Qiu; Y. D. Fan; J. W. Gao (Rock Mechanics and Rock Engineering, 2023)

An overview of 2D metal sulfides and carbides as Na host materials for Na-ion batteries - Javed Rehman; Shiru Lin; Mehwish K. Butt; Xiaofeng Fan; Tamer Khattab; Khaled A. Elsayed; Mohamed F. Shibl (Chemical Engineering Journal, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Combined Static–Dynamic Loading Effect on the Wave Transmission Properties in Rock Masses with Macrojoint and Microdefect - M. Wang; J. L. Shang; L. F. Fan (Rock Mechanics and Rock Engineering, 2022)

The Fate of Erythrocytes after Cerebral Hemorrhage - Fan Xia; Richard F. Keep; Fenghui Ye; Katherine G. Holste; Shu Wan; Guohua Xi; Ya Hua (Translational Stroke Research, 2022)

A fungal mycelium elicitor efficiently improved ginsenoside synthesis during adventitious root culture of Panax ginseng - X. L. An; Y. Yu; M. Z. Fan; X. H. Wu; X. F. Li; X. C. Piao; M. L. Lian (Journal of Plant Biochemistry and Biotechnology, 2022)

Global evaluation of inhibitor impacts on ammonia and nitrous oxide emissions from agricultural soils: A meta‐analysis - Daijia Fan; Wentian He; Ward N. Smith; Craig F. Drury; Rong Jiang; Brian B. Grant; Yaoyao Shi; Daping Song; Yanhua Chen; Xuexia Wang; Ping He; Guoyuan Zou (Global Change Biology, 2022)
Inhibitors are widely considered an efficient tool for reducing nitrogen (N) loss and improving N use efficiency, but their effectiveness is highly variable across agroecosystems. In this study, we synthesized 182 studies (222 sites) worldwide to evaluate the impacts of inhibitors (urease inhibitors [UI], nitrification inhibitors [NI] and combined inhibitors) on crop yields and gaseous N loss (ammonia [NH 3 ] and nitrous oxide [N 2 O] emissions) and explored their responses to different management and environmental factors including inhibitor application timing, fertilization regime, cropping system, water management, soil properties and climatic conditions using subgroup meta‐analysis, meta‐regression and multivariate analyses. The UI were most effective in enhancing crop yields (by 5%) and reducing NH 3 volatilization (by 51%), whereas NI were most effective at reducing N 2 O emissions (by 49%). The application of UI mitigates NH 3 loss and increases crop yields especially in high NH 3 ‐N loss scenarios, whereas NI application would minimize the net N 2 O emissions and the resultant environmental impacts especially in low NH 3 ‐N loss scenarios. Alternatively, the combined application of UI and NI enables producers to balance crop production and environmental conservation goals without pollution tradeoffs. The inhibitor efficacy for decreasing gaseous N loss was dependent upon soil and climatic conditions and management practices. Notably, both meta‐regression and multivariate analyses suggest that inhibitors provide a greater opportunity for reducing fertilizer N inputs in high‐N‐surplus systems and presumably favor crop yield enhancement under soil N deficiency situations. The pursuit of an improved understanding of the interactions between plant‐soil‐climate‐management systems and different types of inhibitors should continue to optimize the effectiveness of inhibitors for reducing environmental losses while increasing productivity.

Determination of Wave Propagation Coefficients of the Granite by High-Speed Digital Image Correlation (HDIC) - Q. H. Yang; L. F. Fan; X. L. Du (Rock Mechanics and Rock Engineering, 2022)

Spatial Failure Mode Analysis of Frozen Sandstone Under Uniaxial Compression Based on CT Technology - L. F. Fan; Y. D. Fan; Y. Xi; J. W. Gao (Rock Mechanics and Rock Engineering, 2022)

Non-attenuation Behavior of Stress Wave Propagation Through a Rock Mass - L. J. Wang; L. F. Fan; X. L. Du (Rock Mechanics and Rock Engineering, 2022)

Critical Angles of Obliquely Incident Stress Wave Through a Single Joint with Different Mediums on Both Sides - L. F. Fan; F. Jiang; M. Wang (Rock Mechanics and Rock Engineering, 2022)

Field engineering application of agricultural farmland surface runoff pollution treatment by combined bioreactor and constructed wetlands - H. Luo; X. Li; Y. Chen; X. Liu; K. Zhang; X. Fu; B. Jiang; R. Xue; J. Yang; M. Li; X. Li; W. Chen; et al. (International Journal of Environmental Science and Technology, 2022)

First report of grapevine polerovirus 1 from grapevines in China - X. D. Fan; Y. F. Dong; Z. P. Zhang; F. Ren; G. J. Hu (Journal of Plant Pathology, 2022)

Equivalent Viscoelastic Behavior of High-Temperature Granite Under Seismic Wave - L. F. Fan; Q. H. Yang; M. Wang; X. L. Du (Rock Mechanics and Rock Engineering, 2022)

Dual-Mesh Three Characteristic Lines Method for Stress Wave Propagation Through a Microdefected Rock Mass with a Thin-Layer Filled Macrojoint - L. F. Fan; M. Wang; X. L. Du (Rock Mechanics and Rock Engineering, 2021)

Environmental impact on the mechanical properties of Porites spp. corals - Molly A. Moynihan; Shahrouz Amini; Nathalie F. Goodkin; Jani T. I. Tanzil; J. Q. Isaiah Chua; Gareth N. Fabbro; Tung-Yung Fan; Daniela N. Schmidt; Ali Miserez (Coral Reefs, 2021)
Despite the economic and ecological importance of corals’ skeletal structure, as well as their predicted vulnerability to future climate change, few studies have examined the skeletal mechanical properties at the nanoscale. As climate change is predicted to alter coral growth and physiology, as well as increase mechanical stress events (e.g., bioerosion, storm frequency), it is crucial to understand how skeletal mechanical properties change with environmental conditions. Moreover, while material properties are intimately linked to the chemical composition of the skeleton, no previous study has examined mechanical properties alongside carbonate geochemical composition. Using Porites coral cores from a wide range of reef environments (Thailand, Singapore, Taiwan), we correlated coral’s micro-mechanical properties with chemical composition. In contrast to previous mechanical measurements of reef-building corals, we document unprecedented variability in the hardness, stiffness, and micro-cracking stress of Porites corals across reef environments, which may significantly decrease the structural integrity of reef substrate. Corals from environments with low salinity and high sedimentation had higher organic content and fractured at lower loads, suggesting that skeletal organic content caused enhanced embrittlement. Within individual coral cores, we observed seasonal variability in skeletal stiffness, and a relationship between high sea surface temperature, increased stiffness, and high-density. Regionally, lower Sr/Ca and higher Mg/Ca coincided with decreased stiffness and hardness, which is likely driven by increased amorphous calcium carbonate and skeletal organic content. If the coral is significantly embrittled, as measured here in samples from Singapore, faster erosion is expected. A decrease in skeletal stiffness will decrease the quality of reef substrate, enhance the rate of bioerosion by predators and borers, and increase colony dislodgement, resulting in widespread loss of structural complexity.

Damage zones induced by in situ stress unloading during excavation of diversion tunnels for the Jinping II hydropower project - Y. Fan; J. W. Zheng; X. Z. Cui; Z. D. Leng; F. Wang; C. C. Lv (Bulletin of Engineering Geology and the Environment, 2021)

Effect of Nonlinear Deformational Macrojoint on Stress Wave Propagation Through a Double-Scale Discontinuous Rock Mass - L. F. Fan; M. Wang; Z. J. Wu (Rock Mechanics and Rock Engineering, 2021)

Robust Subsampling ANOVA Methods for Sensitivity Analysis of Water Resource and Environmental Models - F. Wang; G. H. Huang; Y. Fan; Y. P. Li (Water Resources Management, 2020)

Nitrogen deep placement mitigates methane emissions by regulating methanogens and methanotrophs in no-tillage paddy fields - D. J. Fan; T. Q. Liu; F. Sheng; S. H. Li; C. G. Cao; C. F. Li (Biology and Fertility of Soils, 2020)

Thermal Cycling Effects on Micro-property Variation of Granite by a Spatial Micro-observation - L. F. Fan; J. W. Gao; X. L. Du (Rock Mechanics and Rock Engineering, 2020)

Maternal urinary bisphenol A concentration and thyroid hormone levels of Chinese mothers and newborns by maternal body mass index - Xia Wang; Ning Tang; Shoji F. Nakayama; Pianpian Fan; Zhiwei Liu; Jun Zhang; Fengxiu Ouyang (Environmental Science and Pollution Research, 2020)

Oplopanax elatus adventitious root production through fed-batch culture and their anti-bacterial effects - M. Y. Jin; X. C. Piao; X. H. Wu; M. Z. Fan; X. F. Li; C. R. Yin; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Archaea, the tree of life, and cellular evolution in eukaryotes - Jing Xiao; Lu Fan; Dingfeng Wu; Yanbing Xu; Dengxun Lai; William F. Martin; Ruixin Zhu; Chuanlun Zhang (Science China Earth Sciences, 2019)

Genomic sequencing of a virus representing a novel type within the species Dyopipapillomavirus 1 in an Indian River Lagoon bottlenose dolphin - Galaxia Cortés-Hinojosa; Kuttichantran Subramaniam; James F. X. Wellehan; Terry Fei Fan Ng; Eric Delwart; Stephen D. McCulloch; Juli D. Goldstein; Adam M. Schaefer; Patricia A. Fair; John S. Reif; Gregory D. Bossart; Thomas B. Waltzek (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Detection and genetic characterization of bovine kobuvirus from calves in Egypt - Fakry F. Mohamed; Shimaa M. G. Mansour; Ahmed Orabi; Iman E. El-Araby; Terry Fei Fan Ng; Sunil K. Mor; Sagar M. Goyal (Archives of Virology, 2018)

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

The China Plant Trait Database: toward a comprehensive regional compilation of functional traits for land plants - Han Wang; Sandy P. Harrison; Iain C. Prentice; Yanzheng Yang; Fan Bai; Henrique F. Togashi; Meng Wang; Shuangxi Zhou; Jian Ni (Ecology, 2018)
Plant functional traits provide information about adaptations to climate and environmental conditions, and can be used to explore the existence of alternative plant strategies within ecosystems. Trait data are also increasingly being used to provide parameter estimates for vegetation models. Here we present a new database of plant functional traits from China. Most global climate and vegetation types can be found in China, and thus the database is relevant for global modeling. The China Plant Trait Database contains information on morphometric, physical, chemical, and photosynthetic traits from 122 sites spanning the range from boreal to tropical, and from deserts and steppes through woodlands and forests, including montane vegetation. Data collection at each site was based either on sampling the dominant species or on a stratified sampling of each ecosystem layer. The database contains information on 1,215 unique species, though many species have been sampled at multiple sites. The original field identifications have been taxonomically standardized to the Flora of China. Similarly, derived photosynthetic traits, such as electron‐transport and carboxylation capacities, were calculated using a standardized method. To facilitate trait–environment analyses, the database also contains detailed climate and vegetation information for each site. The data set is released under a Creative Commons BY license. When using the data set, we kindly request that you cite this article, recognizing the hard work that went into collecting the data and the authors' willingness to make it publicly available.

Using remote sensing information to estimate snow hazard and extreme snow load in China - H. M. Mo; H. P. Hong; F. Fan (Natural Hazards, 2017)

EEG artifacts reduction by multivariate empirical mode decomposition and multiscale entropy for monitoring depth of anaesthesia during surgery - Quan Liu; Yi-Feng Chen; Shou-Zen Fan; Maysam F. Abbod; Jiann-Shing Shieh (Medical & Biological Engineering & Computing, 2017)

The role of solubility on the rejection of trace organics by nanofiltration membrane: exemplified with disinfection by-products - Fan-xin Kong; Xiao-mao Wang; Hong-wei Yang; Jin-fu Chen; Chun-mei Guo; Tong Zhang; Yuefeng F. Xie (Environmental Science and Pollution Research, 2017)

Real-time monitoring instrument designed for the deformation and sliding period of colluvial landslides - Y. B. Fan; S. W. Yang; L. K. Xu; S. H. Li; C. Feng; B. F. Liang (Bulletin of Engineering Geology and the Environment, 2017)

First identification of porcine parvovirus 6 in Poland - Jin Cui; Jinghui Fan; Priscilla F. Gerber; Kinga Biernacka; Tomasz Stadejek; Chao-Ting Xiao; Tanja Opriessnig (Virus Genes, 2017)

Extreme snow hazard and ground snow load for China - H. M. Mo; L. Y. Dai; F. Fan; T. Che; H. P. Hong (Natural Hazards, 2016)

Microstructure and Ultrastructure Alterations in the Pallium of Immature Mice Exposed to Cadmium - X. F. Yang; Q. G. Han; D. Y. Liu; H. T. Zhang; G. Y. Fan; J. Y. Ma; Z. L. Wang (Biological Trace Element Research, 2016)

Osteogenic Treatment Initiating a Tissue-Engineered Cartilage Template Hypertrophic Transition - J. Y. Fu; S. Y. Lim; P. F. He; C. J. Fan; D. A. Wang (Annals of Biomedical Engineering, 2016)

Effects of the Land Use Change on Ecosystem Service Value in Chengdu, Western China from 1978 to 2010 - Wen F. Peng; Jie M. Zhou; Shu Y. Fan; Cun J. Yang (Journal of the Indian Society of Remote Sensing, 2016)

Erratum to: Jasmonic Acid Mediates Tomato’s Response to Root Knot Nematodes - J. W. Fan; C. L. Hu; L. N. Zhang; Z. L. Li; F. K. Zhao; S. H. Wang (Journal of Plant Growth Regulation, 2016)

Efficacy of oral moxifloxacin for aerobic vaginitis - C. Wang; C. Han; N. Geng; A. Fan; Y. Wang; Y. Yue; H. Zhang; F. Xue (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

A Real-Time Analysis and Feedback System for Quality Control of Dam Foundation Grouting Engineering - D. H. Zhong; F. G. Yan; M. C. Li; C. X. Huang; K. Fan; J. F. Tang (Rock Mechanics and Rock Engineering, 2015)

Genetics of skin color variation in Europeans: genome-wide association studies with functional follow-up - Fan Liu; Mijke Visser; David L. Duffy; Pirro G. Hysi; Leonie C. Jacobs; Oscar Lao; Kaiyin Zhong; Susan Walsh; Lakshmi Chaitanya; Andreas Wollstein; Gu Zhu; Grant W. Montgomery; et al. (Human Genetics, 2015)

Snow hazard estimation and mapping for a province in northeast China - H. M. Mo; F. Fan; H. P. Hong (Natural Hazards, 2015)

A tortoise-infecting picornavirus expands the host range of the family Picornaviridae - Terry Fei Fan Ng; James F. X. Wellehan; James K. Coleman; Nikola O. Kondov; Xutao Deng; Thomas B. Waltzek; Gábor Reuter; Nick J. Knowles; Eric Delwart (Archives of Virology, 2015)

Efficacy and safety of echinocandins versus triazoles for the prophylaxis and treatment of fungal infections: a meta-analysis of RCTs - J.-F. Wang; Y. Xue; X.-B. Zhu; H. Fan (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Jasmonic Acid Mediates Tomato’s Response to Root Knot Nematodes - J. W. Fan; C. L. Hu; L. N. Zhang; Z. L. Li; F. K. Zhao; S. H. Wang (Journal of Plant Growth Regulation, 2015)

Efficiency of virus elimination from potted apple plants by thermotherapy coupled with shoot-tip grafting - G.-J. Hu; Z.-P. Zhang; Y.-F. Dong; X.-D. Fan; F. Ren; H.-J. Zhu (Australasian Plant Pathology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Resolvin D1 improves survival in experimental sepsis through reducing bacterial load and preventing excessive activation of inflammatory response - F. Chen; X. H. Fan; Y. P. Wu; J. L. Zhu; F. Wang; L. L. Bo; J. B. Li; R. Bao; X. M. Deng (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Transferability of Newly Developed Pear SSR Markers to Other Rosaceae Species - L. Fan; M.-Y. Zhang; Q.-Z. Liu; L.-T. Li; Y. Song; L.-F. Wang; S.-L. Zhang; J. Wu (Plant Molecular Biology Reporter, 2013)

Genetic differ in TLR4 gene polymorphisms and expression involved in Salmonella natural and artificial infection respectively in Chinese native chicken breeds - H. F. Li; Y. Hu; H. Hu; C. Song; J. T. Shu; C. H. Zhu; S. J. Zhang; J. H. Fan; W. W. Chen (Molecular Biology Reports, 2013)

Pulse-based non-thermal plasma (NTP) disrupts the structural characteristics of bacterial biofilms - James R. Ferrell; Fan Shen; Scott F. Grey; Christopher J. Woolverton (Biofouling, 2013)

Diversity of Bacterial Communities Associated with the Indian Ocean Sponge Tsitsikamma favus That Contains the Bioactive Pyrroloiminoquinones, Tsitsikammamine A and B - Tara A. Walmsley; Gwynneth F. Matcher; Fan Zhang; Russell T. Hill; Michael T. Davies-Coleman; Rosemary A. Dorrington (Marine Biotechnology, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Experimental Study on Viscoelastic Behavior of Sedimentary Rock under Dynamic Loading - L. F. Fan; F. Ren; G. W. Ma (Rock Mechanics and Rock Engineering, 2012)

Canine models of Duchenne muscular dystrophy and their use in therapeutic strategies - Joe N. Kornegay; Janet R. Bogan; Daniel J. Bogan; Martin K. Childers; Juan Li; Peter Nghiem; David A. Detwiler; C. Aaron Larsen; Robert W. Grange; Ratna K. Bhavaraju-Sanka; Sandra Tou; Bruce P. Keene; et al. (Mammalian Genome, 2012)

Extraction of spatial-temporal rules from mesoscale eddies in the South China Sea based on rough set theory - Y. Du; X. Fan; Z. He; F. Su; C. Zhou; H. Mao; D. Wang (Ocean Science, 2011)
In this paper, a rough set theory is introduced to represent spatial-temporal relationships and extract the corresponding rules from typical mesoscale-eddy states in the South China Sea (SCS). Three decision attributes are adopted in this study, which make the approach flexible in retrieving spatial-temporal rules with different features. The results demonstrate that this approach is effective, and therefore provides a powerful approach to forecasts in the future studies. Spatial-temporal rules in the SCS indicate that warm eddies following the rules are generally in the southeastern and central SCS around 2000 m isobaths in winter. Their intensity and vorticity are weaker than those of cold eddies. They usually move a shorter distance. By contrast, cold eddies are in 2000 m and deeper regions of the southwestern and northeastern SCS in spring and fall. Their intensity and vorticity are strong. Usually they move a long distance. In winter, a few rules are followed by cold eddies in the northern tip of the basin and southwest of Taiwan Island rather than warm eddies, indicating cold eddies may be well-regulated in the region. Several warm-eddy rules are achieved west of Luzon Island, indicating warm eddies may be well-regulated in the region as well. Otherwise, warm and cold eddies are distributed not only in the jet flow off southern Vietnam induced by intraseasonal wind stress in summer-fall, but also in the northern shallow water, which should be a focus of a future study.

Eight paths of ERK1/2 signalling pathway regulating hepatocyte proliferation in rat liver regeneration - J. W. LI; G. P. WANG; J. Y. FAN; C. F. CHANG; C. S. XU (Journal of Genetics, 2011)

Molecular characterization of the porcine JHDM1A gene associated with average daily gain: evaluation its role in skeletal muscle development and growth - Yong-bo Peng; Bin Fan; Xue-lei Han; Xue-wen Xu; Max. F. Rothschild; Martine Yerle; Bang Liu (Molecular Biology Reports, 2011)

Cellular Toxicity of TiO2 Nanoparticles in Anatase and Rutile Crystal Phase - Chan Jin; Ying Tang; F. Guang Yang; X. Lin Li; Shan Xu; X. Yan Fan; Y. Ying Huang; Y. Ji Yang (Biological Trace Element Research, 2011)

Polymorphism of bovine Y-STR UMN0929 and its correlation with carcass traits in five Chinese beef cattle populations - Y. P. Xin; L. S. Zan; Y. H. Wang; Y. F. Liu; W. Q. Tian; Y. Y. Fan (Molecular Biology Reports, 2011)

Analysis of characteristics of paratyphoid A in 157 Chinese inpatients between 1998 and 2009 - F. Yu; S. Fan; X. Fan; P. Dong; X. Wang; Y. Chen; J. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Transcriptome atlas of eight liver cell types uncovers effects of histidine catabolites on rat liver regeneration - C. F. Chang; J. Y. Fan; F. C. Zhang; J. Ma; C. S. Xu (Journal of Genetics, 2010)

TRAIL-induced apoptosis of human melanoma cells involves activation of caspase-4 - Zhi Gang Mao; Chen Chen Jiang; Fan Yang; Rick F. Thorne; Peter Hersey; Xu Dong Zhang (Apoptosis, 2010)

Identification and molecular characterization of a new potyvirus from Panax notoginseng - Z. L. Yan; L. M. Song; T. Zhou; Y. J. Zhang; M. F. Li; H. F. Li; Z. F. Fan (Archives of Virology, 2010)

Restoration of amphetamine-induced locomotor sensitization in dopamine D1 receptor-deficient mice - Mufida B. El-Ghundi; Theresa Fan; Joanna M. Karasinska; John Yeung; Millee Zhou; Brian F. O’Dowd; Susan R. George (Psychopharmacology, 2010)

Investigation of LDHA and COPB1 as candidate genes for muscle development in the MYOD1 region of pig chromosome 2 - Haifang Qiu; Xuewen Xu; Bing Fan; Max F. Rothschild; Yerle Martin; Bang Liu (Molecular Biology Reports, 2010)

Porcine CSRP3: polymorphism and association analyses with meat quality traits and comparative analyses with CSRP1 and CSRP2 - Xuewen Xu; Haifang Qiu; Zhi-Qiang Du; Bin Fan; Max F. Rothschild; Fan Yuan; Bang Liu (Molecular Biology Reports, 2010)

The transcription factor GATA-2 does not associate with angiographic coronary artery disease in the Ottawa Heart Genomics and Cleveland Clinic GeneBank Studies - Sonny Dandona; Li Chen; Meng Fan; Md Afaque Alam; Olivia Assogba; Melanie Belanger; Kathryn Williams; George A. Wells; W. H. Wilson Tang; Stephen G. Ellis; Stanley L. Hazen; Ruth McPherson; et al. (Human Genetics, 2010)

TheMMP2 gene may be associated withlongissimus dorsi muscle area in the pig (Sus scrofa) - S. K. Onteru; B. Fan; M. F. Rothschild (Journal of Applied Genetics, 2009)

Planning of municipal solid waste management systems under dual uncertainties: a hybrid interval stochastic programming approach - G. H. Cheng; G. H. Huang; Y. P. Li; M. F. Cao; Y. R. Fan (Stochastic Environmental Research and Risk Assessment, 2009)

Orexin A-induced extracellular calcium influx in prefrontal cortex neurons involves L-type calcium channels - J. X. Xia; S. Y. Fan; J. Yan; F. Chen; Y. Li; Z. P. Yu; Z. A. Hu (Journal of Physiology and Biochemistry, 2009)

The genomic sequence and biological properties of Pennisetum mosaic virus, a novel monocot-infecting potyvirus - C. L. Deng; W. J. Wang; Z. Y. Wang; X. Jiang; Y. Y. Cao; T. Zhou; F. R. Wang; H. F. Li; Z. F. Fan (Archives of Virology, 2008)

Analysis of metabolic flux in Escherichia coli expressing human-like collagen in fed-batch culture - Yan E. Luo; Dai D. Fan; Long A. Shang; Hui J. Shi; Xiao X. Ma; Yu Mi; Gui F. Zhao (Biotechnology Letters, 2008)

Short-term carbon dioxide emissions and denitrification losses from soils amended with low-P manure from genetically modified pigs - X. M. Yang; C. F. Drury; T. Q. Zhang; A. Ajakaiye; C. W. Forsberg; M. Z. Fan; J. P. Philip (Nutrient Cycling in Agroecosystems, 2008)

Y chromosomes of prehistoric people along the Yangtze River - Hui Li; Ying Huang; Laura F. Mustavich; Fan Zhang; Jing-Ze Tan; Ling-E Wang; Ji Qian; Meng-He Gao; Li Jin (Human Genetics, 2007)

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

Culture and fusion of pollen protoplasts of Brassica oleracea L. var. italica with haploid mesophyll protoplasts of B. rapa L. ssp. pekinensis - Fan Liu; U. Ryschka; F. Marthe; E. Klocke; G. Schumann; H. Zhao (Protoplasma, 2007)

Effect of intercropping on crop yield and chemical and microbiological properties in rhizosphere of wheat (Triticum aestivum L.), maize (Zea mays L.), and faba bean (Vicia faba L.) - Y. N. Song; F. S. Zhang; P. Marschner; F. L. Fan; H. M. Gao; X. G. Bao; J. H. Sun; L. Li (Biology and Fertility of Soils, 2007)

Regional land surface energy fluxes by satellite remote sensing in the Upper Xilin River Watershed (Inner Mongolia, China) - L. Fan; Sh. Liu; Ch. Bernhofer; H. Liu; F. H. Berger (Theoretical and Applied Climatology, 2007)

The genomic sequence of Wisteria vein mosaic virus and its similarities with other potyviruses - W. X. Liang; L. M. Song; G. Z. Tian; H. F. Li; Z. F. Fan (Archives of Virology, 2006)

Inorganic N Dynamics from Soils Amended with Low-P Manure from Genetically Modified Pigs (EnviropigTM) - X. M. Yang; C. F. Drury; T. Q. Zhang; A. Ajakaiye; C. W. Forsberg; M. Z. Fan; J. P. Philip (Nutrient Cycling in Agroecosystems, 2006)

Analysis of MS2Bnap genomic DNA homologous to MS2 gene from Arabidopsis thaliana in two dominant digenic male sterile accessions of oilseed rape (Brassica napus L.) - S. W. Hu; Y. F. Fan; H. X. Zhao; X. L. Guo; C. Y. Yu; G. L. Sun; C. H. Dong; S. Y. Liu; H. Z. Wang (Theoretical and Applied Genetics, 2006)

A preliminary geological and geochemical study of the Xiangquan thallium deposit, eastern China: the world’s first thallium-only mine - T. F. Zhou; Y. Fan; F. Yuan; M. A. Wu; M. J. Hou; G. Voicu; Q. H. Hu; Q. M. Zhang; S. C. Yue (Mineralogy and Petrology, 2005)

Nitrate tolerance aggravates postischemic myocardial apoptosis and impairs cardiac functional recovery after ischemia - Q. Fan; F. Gao; L. Zhang; T. A. Christopher; B. L. Lopez; X. L. Ma (Apoptosis, 2005)

Single-nucleotide polymorphisms in the C-reactive protein (CRP) gene promoter that affect transcription factor binding, alter transcriptional activity, and associate with differences in baseline serum CRP level - A. J. Szalai; J. Wu; E. M. Lange; M. A. McCrory; C. D. Langefeld; A. Williams; S. O. Zakharkin; V. George; D. B. Allison; G. S. Cooper; F. Xie; Z. Fan; et al. (Journal of Molecular Medicine, 2005)

Immunocytochemical localization of gonadotropins during the development of XX and XY Nile tilapia - F. Sakai; I. Swapna; C. C. Sudhakumari; M. V. N. L. Ganesh; H. Kagawa; T. Kobayashi; H. Fan; Y. Nagahama; B. Senthilkumaran (Fish Physiology and Biochemistry, 2005)

Timing of larval release by the blue coral, Heliopora coerulea, in southern Taiwan - P. J. Liu; T. Y. Fan; C. F. Dai (Coral Reefs, 2005)

Role of insulin in the anti-apoptotic effect of glucose-insulin-potassium in rabbits with acute myocardial ischemia and reperfusion - H. F. Zhang; Q. Fan; X. X. Qian; B. L. Lopez; T. A. Christopher; X. L. Ma; F. Gao (Apoptosis, 2004)

A coupled simple climate model and its global analysis - X. Fan; J.-F. Chou; B.-R. Guo; M. D. Shulski (Theoretical and Applied Climatology, 2004)

Outward K + channels in Brassica chinensis pollen protoplasts are regulated by external and internal pH - L.-M. Fan; Y.-F. Wang; W.-H. Wu (Protoplasma, 2003)

Complete sequence of the genomic RNA of the prevalent strain of a potyvirus infecting maize in China - Z. F. Fan; H. Y. Chen; X. M. Liang; H. F. Li (Archives of Virology, 2003)

Risk factors for medullary thyroid carcinoma: a pooled analysis - Eva Negri; Elaine Ron; Silvia Franceschi; Carlo La Vecchia; Susan Preston-Martin; Laurence Kolonel; Ruth A. Kleinerman; Kiyohiko Mabuchi; Fan Jin; Gun Wingren; Arne Hallquist; Fabio Levi; et al. (Cancer Causes & Control, 2002)

Graph-theoretical identification of pathways for biochemical reactions - H. Seo; D.-Y. Lee; S. Park; L.T. Fan; S. Shafie; B. Bertók; F. Friedler (Biotechnology Letters, 2001)

Endothelial cell survival and apoptosis in the tumor vasculature - W. Liu; S. A. Ahmad; N. Reinmuth; R. M. Shaheen; Y. D. Jung; F. Fan; L. M. Ellis (Apoptosis, 2000)

Therapeutic approaches for ischemia/reperfusion injury in the liver - Chenguang Fan; Ralf M. Zwacka; John F. Engelhardt (Journal of Molecular Medicine, 1999)

Calcium regulation in the human myocardium affected by dilated cardiomyopathy: A structural basis for impaired Ca2+-sensitivity - Sarkis S. Margossian; Page A.W. Anderson; Peter D. Chantler; Mark Deziel; Patrick K. Umeda; Walter F. Stafford; Paul Norton; Ashwani Malhotra; Fan Yang; James B. Caulfield; Henry S. Slayter (Molecular and Cellular Biochemistry, 1999)

Availability of banded triple superphosphate with urea and phosphorus use efficiency by corn - D. S. Ouyang; A. F. MacKenzie; M. X. Fan (Nutrient Cycling in Agroecosystems, 1999)

Application of a Global Analysis Method to a Simplified Climate Model - H. Zhang; X. Fan; M. Xu; J. F. Chou (Theoretical and Applied Climatology, 1998)

Polycyclic Aromatic Hydrocarbons in the Sediments of the Milwaukee Harbor Estuary, Wisconsin, U.S.A. - An Li; Irwan A. Ab Razak; Fan Ni; Michael F. Gin; Erik R. Christensen (Water, Air, & Soil Pollution, 1998)

Differential requirements of two insect cell lines for growth in serum-free medium - J. L. Vaughn; F. Fan (In Vitro Cellular & Developmental Biology - Animal, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)